The effectiveness of a program based on the constructivist approach to teaching jurisprudence in developing health concepts for first-year secondary students in Amran Governorate in the Republic of Yemen - Hamdan, Adnan Ibrahim Mohammed (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the effectiveness of a program based on the constructivist approach to teaching jurisprudence in developing health concepts for first-year secondary school students in Amran Governorate in the Republic of Yemen. To achieve the objectives of this study, the researcher prepared a list of health concepts consisting of (40) sub-concepts, distributed in (7) main fields, and built a program based on the constructivist approach to teach the subject of Islamic jurisprudence related to the development of health concepts. The researcher used the semi-experimental approach with a one-group design. The instrument of this study was a test including health concepts. The sample of the study consisted of (60) male and female students who were chosen intentionally from (3) three various schools of first-year secondary school students in Amran Governorate. The study was conducted during the second semester of the 2022/2023 academic year In Amran. The study concluded the following results: There were statistically significant differences at the level of (0.001) between the average scores of the experimental group members in the pre-and post-applications of the health concepts test. The differences were in the direction of the post-application. The results also revealed the effectiveness of the program based on the constructivist approach to teaching jurisprudence to develop health concepts for first-year secondary school students in Amran City. Therefore, the study recommended benefiting from the list of health concepts that this study concluded when preparing health development programs to teach any course of the branches of Islamic education for the secondary stage. Additionally, the study recommended including the concepts of health and awareness in the Islamic education curriculum in the secondary stage and providing students with positive attitudes toward them.
Keywords: program; constructivist approach; jurisprudence; health concepts; first-grade secondary